Contribution of cell wall degrading enzymes to pathogenesis of Fusarium graminearum: a review - Kikot, G.E.; Hours, R.A.; Alconada, T.M.
Plant-pathogenic fungi produce an array of extracellular hydrolytic enzymes that enable them to penetrate and infect the host tissue; these enzymes are collectively called cell wall-degrading enzymes (CWDE). They may contribute to pathogenesis by degrading wax, cuticle and cell walls, thus aiding tissue invasion and pathogen dissemination. Furthermore, they can act as elicitors of host defense reaction. Fusarium head blight (FHB)is a disease caused principally by Fusarium graminearum on crops, occurring all over the world. Important economic losses on wheat-growing areas have been registered by altering quality parameters of grains. Significant progress has been made in understanding the infection process from F. graminearum on wheat, based on genomic technologies. The virulence degree of this phytopathogen on crops could arise from differences in the production of extracellular enzymes, factors controlling the establishment of infection. Fusarium graminearum isolates from different geographical areas have been examined, and a combination of morphological and molecular data allowed the division of fungi in diverse groups, which have been related to the variation in pathogenicity. In most studied cases there is a correlation between the presence of pectic enzymes, disease symptom and virulence, being also their production decisive in the infection process.
Keywords: FUSARIUM GRAMINEARUM; FUSARIUM HEAD BLIGHT; CEREAL GRAIN; EXTRACELLULAR ENZYMES; PECTINASES